PENINGKATAN HASIL BELAJAR BILANGAN BULAT MELALUI MODEL PEMBELAJARAN KI HAJAR DEWANTARA PADA SISWA DISKALKULIA - Desi Erfan (LPMP Provinsi DKI Jakarta, 2022)
Students with dyscalculia can be found in most schools. They have average intelligence and have difficulty learning mathematics. This study aims to improve the mathematics learning outcomes of dyscalculia students about addition and subtraction of integers in grade 6 through Ki Hajar Dewantara's fun learning model. This research was conducted at SDN Duren Sawit 05 Jakarta involving 10 dyscalculia students. This research uses classroom action research method in 2 cycles. The results showed that the Ki Hajar Dewantara learning model could improve the learning outcomes of addition and subtraction of integers, the value of knowledge from 54 to 90, the value of skills from 63 to 97, and the value of attitudes from 58 to 96. The Among Ki Hajar Dewantara learning model used This research includes 6 activities, namely: 1) question-and-answer-based presentations, 2) video learning, 3) props from used goods, 4) number line simulation with tiles, 5) visualization of mathematical symbols with colored markers, and 6) learning with songs and chants. The conclusion of the research is that Ki Hajar Dewantara's learning model can improve the learning outcomes of addition and subtraction of integers.